Pengembangan Budaya Organisasi Lembaga Pendidikan Islam (Studi Kasus di TK Terpadu Budi Mulia Dua Seturan Yogyakarta) - Dina Islamika (STID Raudlatul Iman Sumenep, 2019)
Organization is a system in which there are various elements that are interconnected with each other. The organizational culture contains the overall understanding of social values, social norms, ways, habits, behaviors and science as well as the overall social, religious, and other structures, all intellectual and artistic statements that characterize a society. Organizational culture is the overall beliefs, feelings, behaviors, and symbols that characterize an organization. More specifically, organizational culture is defined as the various philosophies, ideologies, beliefs, feelings, assumptions, expectations, attitudes, norms, and values.Based on several definitions above can be concluded that the organizational culture in educational institutions is the meaning of together with all members of the organization in an educational institution related to values, norms, beliefs, traditions and unique ways of thinking embraced and visible in their behavior, thus distinguish between one educational institution With other educational institutions. Organisasi merupakan suatu sistem yang didalamnya terdapat berbagai unsur yang saling keterkaitan antara satu sama lainnya. Budaya organisasi mengandung keseluruhan pengertian nilai sosial, norma sosial, cara, kebiasaan, perilaku dan ilmu pengetahuan serta keseluruhan struktur-struktur sosial, religius, dan lain-lain, segala pernyataan intelektual dan artistik yang menjadi ciri khas suatu masyarakat. Budaya organisasi adalah keseluruhan kepercayaan, perasaan, perilaku, dan simbol yang mengkarakteristikkan suatu organisasi. Lebih spesifiknya, budaya organisasi didefinisikan sebagai berbagai filsafat, ideology, kepercayaan, perasaan, asumsi, harapan, sikap, norma, dan nilai. Berdasarkan beberapa defenisi diatas dapat disimpulkan bahwa budaya organisasi di lembaga pendidikan adalah pemaknaan bersama seluruh anggota organisasi di suatu lembaga pendidikan yang berkaitan dengan nilai, norma, keyakinan, tradisi dan cara berfikir unik yang dianutnya dan tampak dalam perilaku mereka, sehingga membedakan antara satu lembaga pendidikan dengan lembaga pendidikan yang lain.